Proposed solution for the non-performing loans in the portuguese banking system - Santos, Bárbara Magalhães (2018)
This paper aims to propose a solution for the current problem of Non-Performing Loans (NPLs) in the Portuguese banking system. The analysis starts with an overview of the theoretical responses to an overall NPL problem. This is followed by a description of the relevant events in the last decade within the Portuguese banking system and of the solution currently being studied by the Portuguese government. The paper concludes that the solution has severe flaws, and proposes an alternative solution that consists on a centralized asset management company.